Pentingnya Guru dalam Menguasai Substansi Materi Pembelajaran - Dorlan Naibaho; Epa Gracelia Ferals Sitorus (Pusat Riset dan Inovasi Nasional, 2023)
A teacher is a person who can be defined as one of the main factors and actors in the success of education. As an educator, of course, teachers are required to have multiple roles as informators, transmitters, organizers, motivators, initiators, directors or guides, facilitators, and mediators. In teachers have at least four competencies, namely: pedagogic competence, personality competence, social competence, professional competence. When carrying out Teaching and Learning Process Activities, the teacher of course has prepared himself, but problems occur if the teacher does not master the substance or subject / content of the material to be taught, as a result the teacher only dictates or plagiarizes the material that has been available from the book. This study aims to describe the importance of teachers in mastering the substance of learning material. This study used a qualitative approach with a systematic review method. This study used a qualitative approach with a systematic review method. Various sources are presented in a balanced manner and used as research references, as well as observed and criticized in order to obtain an in-depth study of the importance of teachers mastering the substance of learning material. The current Merdeka Belajar curriculum demands student-centered learning. Teachers are said to be facilitators and mediators, it does not mean that students are required to seek knowledge on their own, but teachers are required to understand and even master the substance of learning material and must broaden their horizons by multiplying references from the internet and self-practice tests first, so that during the teaching and learning process takes place effectively and communicatively.